Influence of Sulfur and Additives on Wear of Exhaust Valve Seat of Cylinder Head. (17th July 2021) - Zhao, Jianping; Zhang, Shunli; Dou, Zhenhuan; Sun, YuBo; Wan, Jiangkun; Du, Lei
Abstract : In this paper, taking a certain type of high-power diesel engine exhaust valve abnormal wear phenomenon as an example, we conduct research on the exhaust valve surface micromorphology characteristics, contact surface accumulation products, additive transition layer, and combustion test. These passed diesel sulfur content comparative test, diesel additive composition analysis, and high-sulfur-content and low-sulfur-content diesel and diesel oil additive action test. At present, there is no authoritative research on the influence of sulfur content in diesel on valve seat wear of high-power diesel engines, and the protection mechanism of diesel additives on the valve seat is not clear. The sulfur in diesel, like the lead in gasoline, has long been known to resist wear in the valve seats of high-power diesel engines; just as gasoline additives compensate for the loss of lead, diesel oil additives seem to compensate for the loss of sulfur. Tests show that a uniform carbon deposition layer is formed on the contact surface after the diesel is burned, and the carbon deposition layer is more densely and uniformly adsorbed on the contact surface under the action of diesel additives to form an antiwear layer. Tests also show that the sulfur in diesel has no effect on the wear resistance of the valve seat.